SOME ARGUMENTS AGAINST THE INTER-PERIOD ALLOCATION OF INCOME TAXES. - Hill, Thomas M. (The Accounting Review, 1957)
Abstract In an article entitled Income Taxes in Financial Statements appearing in the April 1957 issue of The Accounting Review, Maurice Moonitz presents the case for the allocation of taxes on business income. The basic proposition is essentially that embodied in Accounting Research Bulletin Number 23 of December 1944. Moonitz's contribution lies in the orderly development of a supporting rationale. The object of this paper is to rebut these arguments and to develop from this rebuttal an alternate and opposing thesis. Although Moonitz considers the intra-period application of the accrual doctrine, attention will here be directed to the admittedly more important question of inter-period income tax allocation. There is no doubt that current practice defines the business income tax as a cost. However, the majority position is not invulnerable. In response to Moonitz's challenge, it can be asserted that a dollar of corporate income tax differs from a dollar of corporate wages in that the former is paid only if period revenues exceed period costs. In this respect, the tax dollar is suspiciously like the dividend dollar.